2012
DOI: 10.1111/ajco.12035
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase II randomized study of Cremophor‐free polymeric nanoparticle formulation of paclitaxel in women with locally advanced and/or metastatic breast cancer after failure of anthracycline

Abstract: NP is well tolerated and can be safely administered without any premedication in comparison to conventional paclitaxel, which requires the use of premedication before administration. NP demonstrates promising efficacy with a favorable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…We ultimately identified 22 independent studies published between March 2005 and March 2020 [9,10,12,13,16,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. A flow chart representing selection of studies is shown in Figure 1 Table 1.…”
Section: Identification and Characteristics Of Studiesmentioning
confidence: 99%
“…We ultimately identified 22 independent studies published between March 2005 and March 2020 [9,10,12,13,16,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. A flow chart representing selection of studies is shown in Figure 1 Table 1.…”
Section: Identification and Characteristics Of Studiesmentioning
confidence: 99%
“…We ultimately identi ed 22 independent studies published between March 2005 and March 2020 [9,10,12,13,16,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. A ow chart representing selection of studies is shown in Figure 1.…”
Section: Identi Cation and Characteristics Of Studiesmentioning
confidence: 99%
“…The incidence of musculoskeletal events, gastrointestinal toxicity, and skin/subcutaneous toxicity were comparable in all the treatment arms. Overall, the nanoparticle polymer-based paclitaxel formulation was well-tolerated and could be safely administered without any premedication ( 55 ).…”
Section: Paclitaxelmentioning
confidence: 99%